2016
DOI: 10.3928/23258160-20160707-06
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Segment Distortion in Ultra-Widefield Imaging Compared to Conventional Modalities

Abstract: Optos incorporates a consistent horizontal stretch to images. Combining images taken at right angles reduces the distortion. [Ophthalmic Surg Lasers Imaging Retina. 2016;47:644-651.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Nicholson et al. () recently showed that UWF were distorted in the horizontal plane, but other authors found a nonuniformly distributed deformation of the images (Daftari et al. ; Muttuvelu & Kiilgaard ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nicholson et al. () recently showed that UWF were distorted in the horizontal plane, but other authors found a nonuniformly distributed deformation of the images (Daftari et al. ; Muttuvelu & Kiilgaard ).…”
Section: Discussionmentioning
confidence: 97%
“…Three of these concerned montages of multiple SF images, and it is therefore impossible herein to distinguish whether this was due to the reconstruction or the UWF, but in the fourth case, all measurements were performed in the central SF, leaving the distortion solely explainable by the UWF. Nicholson et al (2016) recently showed that UWF were distorted in the horizontal plane, but other authors found a nonuniformly distributed deformation of the images (Daftari et al 2010;Muttuvelu & Kiilgaard 2019). More generally, distortions may be explained by the fact that fundus imaging is a projection of a curved surface on a plane surface, as seen on a world map.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous methods have been utilised to study image distortion in ultra-widefield imaging but this is the first reported study whereby 3-D printed model eyes have been used with the analysis of the influence of varying axial lengths on the image produced. [8][9][10] Previous reports have used known sizes such as the Argus implant or the optic disc but using a 3-D printed model eye, more detailed analyses can be performed. 9,10,16 From our study, we have identified several key findings.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Previous reports have used known sizes such as the Argus implant or the optic disc but using a 3-D printed model eye, more detailed analyses can be performed. 9,10,16 From our study, we have identified several key findings. Firstly, despite software correction, there is still an increasing distortion towards the periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation